From plate to post: Exploring the impact of foodstagramming on Greece’s travel destination image - Bilro, R. G.; Koutoulaki, E. (Consumer brand relationships in tourism: An international perspective, 2024)
This chapter aims to explore the influence of food-related content on social media on the destination image of Greece, emphasizing the value of food as a unique and distinguishing element of tourist destinations. The study uses a focus group technique to collect ideas from a sample of young culinary tourists belonging to the target group of Millennials and Generation Z. The focus group provides valuable insights into the relationship between Greek gastronomy, traveling, and social media, with a specific focus on the impact of Instagram on destination choice and travel planning. The findings demonstrate a significant impact of social media food content on the behavior, travel choices, and motivations of young gastronomic tourists, underscoring the importance of this type of content in developing gastronomic tourism and improving the destination image of Greece.